The Development of Service Desk Application (SDA) as a Media to Improve Care Services and Asset Improvement in the University. Issue 1 (March 2020) - Purwanto, Riyadi; Yamin, Muhammad; Jaya, Laode Muh. Golok; Gunawan, Yuspian
Abstract: An asset is a wealth. Assets at universities in the form of facilities and infrastructure are used as learning media. To ensure the assets are in good condition, assets must be managed properly. Universities is an entity that has various types of assets and distributed in various work units. Maintenance technicians have the task of carrying out maintenance and repair of assets. Care and repair history must be recorded. Requests for repairing damaged assets or having problems must be dealt with quickly. However, some universities are still implementing conventional systems. The purpose of this study is to develop Service Desk Application (SDA) as medium to improve maintenance and repair services for campus assets quickly and precisely. SDA is a centralized service application that is used to handle repair requests from customers. The results showed that SDA can monitor the status and progress of asset maintenance and control the performance of technicians so that they can complete work quickly and according to procedures, SDA serves as a useful knowledge-based management to enrich knowledge so that if there are problems with similar assets, then the solution to the problem can be immediately known.